Will Chinese working system be convergent to the West: the effects of two-child policy on flexible working system in China - Zhang, Wenxin (2016)
This dissertation argues for a diverse understanding to the two-child policy and its effects on Chinese working system. This is discussed within the context of Chinese youths’ opinion on the policy and the experiences of work-life balance. The key aim of this research is to specify the opinion towards the two-child policy, focusing almost exclusively on female, childcare and working system to explicit the possibility of Chinese working system being convergent to the West. Primary data were collected in the form of semi-structure, in-depth interviews with 10 Chinese participants who were studying in the University of Nottingham and planning to work back to China, five of them were male and five were female. The empirical data have indicated that both male and female have similar attitudes towards the two-child policy, most of them would like to have two child and had a high level of demand of time and energy which can be putted into their childcare and family. It is argued that a deeper understanding of the effects of two-child policy for both employers and employees is necessary. It is important to the employees’ needs, realize the potential management problems, learn from the West, introduce the flexible working system properly. By acknowledging various limitations of the study, a more realistic and sophisticated analysis can be taken in the further research.